Ajaran Tri Kaya Parisudha Dan Catur Guru Dalam Lontar Wirata Parwa Sebagai Upaya Penyuluh Meningkatkan Sradha Dan Bhakti Umat Hindu Dimasa Pandemi Covid-19 - I Nyoman Ariyoga (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2020)
At this time people around the world are struggling to deal with the Corona Virus pandemic which has claimed many victims. The community must remain productive to meet their needs, worship and so on by still paying attention to health protocols. The role of counseling on Hinduism is very necessary, apart from increasing the preparedness of the community to face the Covid 19 pandemic, to pay attention to the health procedures that have been recommended by the government. Efforts to cultivate Sradha and Bhakti people in religious life are also very important to focus more on carrying out prayer services in their respective homes. In this paper, it focuses on the application of the teachings of Tri Kaya Parisudha and Catur Guru by the Pandavas during the incognito period in the Matsya Kingdom in Lontar Wirata Parwa. This research is a textual research, which uses text as the main source. This was done solely to find out the mindset and chronology of Hindu thought in the past. As in Lontar Wirata Parwa, there are teachings of Tri Kaya Parisudha which consist of Kayika Parisudha, Wacika Parisudha and Manacika Parisudha. Mean while, the teachings Catur Guru consist of Guru Swadyaya, Guru Rupaka, Guru Pengajian and Guru Wisesa. Referring to these teachings, it is expected to make guidelines in life so as not to deviate from the behavior taught by Religion. And later it will be used as a reference in the efforts to develop Sradha and Bhakti for Hindus during the Covid-19 era. Keywords: Teachings of Tri Kaya Parisudha and Catur Guru, Lontar Wirata Parwa, Sradha and Bhakti, the Covid-19 Pandemic.